Message in a bottle - Arif NurMohamad; Monk, Dave (Australia: BBC Learning, 2004)
This films is about two new companies, Mecca Cola and Qibla Cola try to break coca-cola's monopoly
Executive producer, Rath Pitt
Narrator: Andrew Scarborough
Keywords: Coca-Cola Company; Soft drink industry; Soft drinks -- Marketing